2022-RA-868-ESGO Risk for contralateral non sentinel metastases in patients with a unilateral positive sentinel lymph node in primary vulvar cancer- a subgroup analysis of the AGO-VOP.2 QS vulva study. (20th October 2022) - Prieske, Katharina; Hampl, Monika; Jaeger, Anna; Eulenburg, Christine; Schmalfeldt, Barbara; Fürst, Sophie; Klapdor, Ruediger; Heublein, Sabine; Gass, Paul; Rohner, Annika; Canzler, Ulrich; Becker, Sven; et al.
Abstract : Introduction/Background: The need for contralateral full groin dissection after bilateral sentinelnode biopsy (SNB) with only unilateral detection of a macrometastasis is unclear. Bilateral inguino-femoral lymphadenectomy (if- LAE) is recommended by German guidelines to avoid groin recurrences which are associated with high morbidity. Few unicenter, retrospective analyses have looked at the risk of contralateral non-sentinel (SNL) metastases with conflicting results. Methodology: The AGO VOP.2 QS vulva study is a retrospective, multicenter study. Within the study, therapeutic data from n=306 patients, diagnosed with primary groin node positive vulvar squamous cell carcinoma (VSCC) between 2017–2019 at 33 gynecologic cancer centers in Germany were collected. In the current subgroup analysis, only patients with bilateral SNB and unilateral positive SNL were included. Results: Of 306 documented groin node positive patients, 137 received bilateral SNB. Of these, 98 had unilateral positive SNL.58/98 (59.18%) received a consecutive bilateral if- LAE. 30/98 (30.61%) underwent unilateral if- LAE and 10/98 (10.2%) had none. Of 98 patients with unilateral positive SNL, two patients (2.04%) showed positive contralateral non-SNL. In the first patient with a midline VSCC a contralateral non-SNL metastasis was detected, despite two negative SNLs in this groin. Bilateral LAE and adjuvant chemoradiation of groins and pelvis were performed and there is no sign of recurrence 18 months after first diagnosis (FD). In the second patient one non-SNL metastasis of 2 mm was detected during LAE after a negative SNL node in the same groin. This patient received radiation to vulva and groins. She suffered from isolated groin recurrence in the groin were the SNL metastasis was initially detected, 11 months after FD. Conclusion: In this large multicentre retrospective trial the risk of contralateral non-SNL metastasis is low. Therefore, morbidity should be carefully balanced against oncologic safety and omission of contralateral LAE should be considered, especially in multimorbid or obese patients.